Use of Project-Based Learning for Teaching Software Quality: College Students Perception - Treviño Villalobos, Marlen (2023)
The Computer Engineering Major at the Tecnológico de Costa Rica conducts a program called the Pilot Plan for Business-Linked Training. For this reason, in the Software Quality Assurance course, a test plan was designed and used by students in an authentic and real software project of a company with a project-based learning strategy. Regarding the objective of this research, it consisted of presenting the implementation of the project-based learning methodology in the Software Quality Assurance course and knowing the perception of the students about the developed process. Moreover, the researcher applied a methodological process through the quantitative approach and worked with a population of 50 students, to whom the investigator applied a digital survey. Thus, the author studied the data through a descriptive statistical analysis, a correlational analysis, and a non-parametric test. The results indicated that the strategy was properly implemented in a 100% virtual modality. In addition, the opinion expressed by the students was positive and, for the most part, they recommend the educational strategy.